Risk Factors for Wheezing in Primary Health Care Settings in the Tropics - Mallol-Villablanca, E (American College of Allergy, Asthma and Immunology, 2020)
Background: The International Study of Wheezing in Infants (EISL) is a cross-sectional, population-based study, based on ISAAC (http://www.isaac.auckland.ac.nz). It uses a validated questionnaire on early wheezing and risk/protective factors. Objective: To apply the EISL questionnaire regarding wheezing events in 0- to 12-month-old infants with or without atopic background searching for risk factors in the tropics. Methods: The population was toddlers coming in for a checkup or 12-months’ vaccination in primary health care clinics of a tropical city. Apart from child factors (eg, daycare attendance), we evaluated home factors (eg, air conditioning, bathroom, carpet, >6 persons, pollution) and mothers factors (eg, education level, employment, cellphone). Data analysis was descriptive and case-control, with as cases atopic (AW) or non-atopic (NAW) wheezing children vs healthy controls. Wheezing-associated factors were evaluated using multivariate analysis, adjusted for the relation of AW/NAW with factors that were significant in prior univariate analysis. Results: The study included 999 toddlers. Any wheeze: 31.3%, recurrent wheeze (≥3 episodes): 12.1%. Major risk factors for AW (OR; 95%CI) included smoking (11.39; 2.36-54.99), common cold before 3 months of life (3.72; 2.59-5.36), mold (3.48; 2.28-5.30), kitchen indoors (2.40; 1.27-4.54), and pets (1.69; 1.09-2.62); breastfeeding was almost protective. For NAW, common cold and pets were risk factors, but cesarean section (0.44; 0.23-0.82), more than 1 sibling (0.33; 0.18-0.61), and breastfeeding for longer than 3 months (0.50; 0.28-0.91) were protective. Conclusion: Wheezing is a health care burden. We found potential new risk factors for AW, some possibly unique for tropical climates. We suggest testing several hypotheses: could early AW be reduced in the tropics by attacking mold growth? Enhancing cooking place ventilation? Keeping pets outside? Or by postponing daycare attendance until after 4 months of age and avoiding (passive) smoking during pregnancy? © 2019 American College of Allergy, Asthma & Immunology